Integrative motivation and speaking achievement: A study of Indonesian L2 learners of English - Saragih, Tiofani Yasimawarni; Subekti, Adaninggar Septi (LITERA, 2023)
The study investigates English as a second/foreign language (L2) learners' integrative motivation and its influence on their L2 speaking achievement. It employed a survey method and used speaking test scores to measure L2 speaking achievement. 188 Indonesian L2 learners from non-English departments participated in this study. This study was conducted to fill the gap in the motivation literature which underrecruited L2 learners from non-English departments and lacked quantitative studies involving a sufficient number of such participants in the Indonesian context. Using descriptive statistics on SPSS, the study found that learners generally reported a high level of integrative motivation. Their motivation to make friends with native English speakers was slightly higher than their motivation to learn about native speakers' cultures and to be involved in native speakers' communities. Through bivariate linear regression, the study found that learners' integrative motivation did not influence their L2 speaking achievement. These findings suggested despite integrative motivation being established in L2 literature, it did not always translate into motivated behaviours. This also calls for a re-examination of some pedagogical practices orienting towards native speakers and their cultures.